2017
DOI: 10.1093/sleep/zsx114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Memory Retrieval in Slow-Wave Sleep

Abstract: Study ObjectivesMemories are strengthened during sleep. The benefits of sleep for memory can be enhanced by re-exposing the sleeping brain to auditory cues; a technique known as targeted memory reactivation (TMR). Prior studies have not assessed the nature of the retrieval mechanisms underpinning TMR: the matching process between auditory stimuli encountered during sleep and previously encoded memories. We carried out two experiments to address this issue.MethodsIn Experiment 1, participants associated words w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
1
20
2
Order By: Relevance
“…Furthermore priming based on similarity at a surface level may have a slower, more effortful mechanism than priming that relies on match at an abstract level (e.g., McLennan & Luce, 2005). Our proposal based on the current evidence is that word-meaning priming is supported the same medial temporal lobe circuitry that underpins paired-associate learning, which at least in part may have a more abstract element (Cairney, Sobczak, Lindsay, & Gaskell, 2017), linking the words at a lexical or conceptual level rather than a more superficial level.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore priming based on similarity at a surface level may have a slower, more effortful mechanism than priming that relies on match at an abstract level (e.g., McLennan & Luce, 2005). Our proposal based on the current evidence is that word-meaning priming is supported the same medial temporal lobe circuitry that underpins paired-associate learning, which at least in part may have a more abstract element (Cairney, Sobczak, Lindsay, & Gaskell, 2017), linking the words at a lexical or conceptual level rather than a more superficial level.…”
Section: Discussionmentioning
confidence: 72%
“…Likewise, replaying verbal foreign language cues facilitates the retrieval of cued (vs. non-cued) vocabulary translations 19,20 . These findings are supplemented by a range of behavioural 21,22 , neuropsychological 23 and neuroimaging 24 studies, indicating that TMR can be used to selectively strengthen declarative memories.…”
Section: Introductionmentioning
confidence: 94%
“…Previous research has established the role of non-rapid eye movement (NREM) sleep, along with its electrophysiological signatures of slow oscillations (SOs) and spindles, for memory consolidation [ 1 , 2 , 3 , 4 ]. In related work, experimental manipulations have demonstrated that NREM sleep provides a window of opportunity to selectively strengthen particular memory traces via the delivery of auditory cues [ 5 , 6 , 7 , 8 , 9 , 10 ], a procedure known as targeted memory reactivation (TMR). It has remained unclear, however, whether TMR triggers the brain’s endogenous consolidation mechanisms (linked to SOs and/or spindles) and whether those mechanisms in turn mediate effective processing of mnemonic information.…”
mentioning
confidence: 99%